Solid pseudopapillary neoplasm of the pancreas with hepatic metastases: problems and strategies - Li, Xiaocheng; Ren, Jiaxin; Ke, Jianji; Jiang, Peng; Guo, Liang; Zhang, Li; Han, Wei; Liu, Yahui; Ji, Bai (Frontiers in Oncology, 2024)
Background Solid pseudopapillary neoplasms of the pancreas with hepatic metastases are infrequent and difficult to diagnose, and treatment is uncertain. Methods A retrospective analysis of clinical data from patients with pancreatic solid pseudopapillary neoplasm (SPN) hepatic metastases who underwent surgery at the First Hospital of Jilin University from January 2005 to December 2021 was conducted. A total of 287 patients with SPN were included in the study, of which 8 (3%) developed liver metastases, all of whom were treated surgically and recovered well after surgery. The clinical presentation, imaging features, surgical treatment, histopathological examination, and postoperative follow-up data (mean 70 months; range 28–138 months) of the patients were recorded and analyzed. Clinical response strategies can be derived by reviewing previous studies on hepatic metastases of SPNs. Results For resectable hepatic metastases from pancreatic solid pseudopapillary neoplasms, early surgery with total resection of the primary tumor and metastasis has shown great efficiency and is associated with patient good prognosis. In patients presenting unresectable hepatic metastases, aggressive tumor reduction surgery resulted in the alleviation of clinical symptoms and reduction of tumor burden while potentially achieving long-term survival. Conclusion For hepatic metastases of SPNs, a preoperative liver tissue biopsy is beneficial for a definitive diagnosis. Surgery demonstrates excellent therapeutic efficacy and is considered the preferred curative treatment approach. This paper presents clinical experiences with SPN-related hepatic metastases at the Affiliated Hospital of Jilin University, which can be used to guide patient counseling in clinical practice.